Self‐assembled human placental model from trophoblast stem cells in a dynamic organ‐on‐a‐chip system - Cao, Rongkai; Wang, Yaqing; Liu, Jiayue; Rong, Lujuan; Qin, Jianhua (Cell proliferation, 2023)
The placental barrier plays a key role in protecting the developing fetus from xenobiotics and exchanging substances between the fetus and mother. However, the trophoblast cell lines and animal models are often inadequate to recapitulate the key architecture and functional characteristics of human placental barrier. Here, we described a biomimetic placental barrier model from human trophoblast stem cells (hTSCs) in a perfused organ chip system. The placental barrier was constructed by co‐culture of hTSCs and endothelial cells on the opposite sides of a collagen‐coated membrane on chip. hTSCs can differentiate into cytotrophoblasts (CT) and syncytiotrophoblast (ST), which self‐assembled into bilayered trophoblastic epithelium with placental microvilli‐like structure under dynamic cultures. The formed placental barrier displayed dense microvilli, higher level secretion of human chorionic gonadotropin (hCG), enhanced glucose transport activity. Moreover, RNA‐seq analysis revealed upregulated ST expression and activation of trophoblast differentiation‐related signalling pathways. These results indicated the key role of fluid flow in promoting trophoblast syncytialization and placental early development. After exposure to mono‐2‐ethylhexyl phthalate, one of the endocrine disrupting chemicals, the model showed inhibited hCG production and disturbed ST formation in trophoblastic epithelium, suggesting impaired placental structure and function elicited by environmental toxicants. Collectively, the hTSCs‐derived placental model can recapitulate placenta physiology and pathological response to external stimuli in a biomimetic manner, which is useful for the study of placental biology and associated diseases. Human placental barrier is consisted of trophoblastic layer, basal lamina, and the fetal capillaries in vivo. We developed a biomimetic placental barrier‐on‐a‐chip model by self‐assembly of human trophoblast stem cells in a dynamic microenvironment, recapitulating the key architecture and functions of human placental villi.